The Changing Transmission of Uncertainty Shocks in the U.S. Issue 2 (3rd April 2018) - Mumtaz, Haroon; Theodoridis, Konstantinos
Abstract : This article investigates if the impact of uncertainty shocks on the U.S. economy has changed over time. To this end, we develop an extended factor augmented vector autoregression (VAR) model that simultaneously allows the estimation of a measure of uncertainty and its time-varying impact on a range of variables. We find that the impact of uncertainty shocks on real activity and financial variables has declined systematically over time. In contrast, the response of inflation and the short-term interest rate to this shock has remained fairly stable. Simulations from a nonlinear dynamic stochastic general equilibrium (DSGE) model suggest that these empirical results are consistent with an increase in the monetary authorities' antiinflation stance and a "flattening" of the Phillips curve. Supplementary materials for this article are available online.